2021
DOI: 10.3390/microorganisms9040747
|View full text |Cite
|
Sign up to set email alerts
|

Production of Monacolin K in Monascus pilosus: Comparison between Industrial Strains and Analysis of Its Gene Clusters

Abstract: Monascus pilosus strains are widely applied to yield a cholesterol synthesis inhibitor monacolin K (MK), also called lovastatin (LOV). However, the mechanism of MK production by M. pilosus strains is still unclear. In this study, we firstly confirmed four Monascus strains, MS-1, YDJ-1, YDJ-2, and K104061, isolated from commercial MK products as M. pilosus and compared their abilities to produce MK in solid-state and liquid-state cultures. Then, we sequenced and analyzed their genomes and MK biosynthetic gene c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…On the other hand, gene sequencing similarity of monacolin K among Monascus species was highly homologous. This finding is in agreement with the study of Dai et al, who compared the monacolin K gene cluster of seven M. pilosus and M. ruber strains (Dai et al 2021 ). The highly homologous citrinin genes in Monascus spp.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, gene sequencing similarity of monacolin K among Monascus species was highly homologous. This finding is in agreement with the study of Dai et al, who compared the monacolin K gene cluster of seven M. pilosus and M. ruber strains (Dai et al 2021 ). The highly homologous citrinin genes in Monascus spp.…”
Section: Discussionsupporting
confidence: 93%
“…The gene sequences of the BGCs in M. ruber FWB13, M. ruber KACC 46666, M. ruber GA, and M. pilosus MS-1 were found to be highly similar to the reference BGC. M. pilosus YDJ1, M. pilosus YDJ2, and M. pilosus K104061 were isolated from commercial MK products and found to be capable of producing MK ( Dai et al, 2021 ), but antiSMASH or BLAST searches revealed incomplete BGC sequences in their genomes. MokH was absent in M. pilosus K104061, and MokE was missing from M. pilosus YDJ1’s BGC.…”
Section: Resultsmentioning
confidence: 99%
“…The phenotype-based identification schemes in Monascus were difficult to match with the results obtained by ITS, partial LSU and/or β-tubulin gene sequencing ( Patakova, 2013 ), especially in the case of single-gene locus-based phylogenetics. For example, Dai et al (2021) inferred a Neighbor-Joining tree using ITS sequences, which revealed that several isolates from M. pilosus , M. fuliginosus , M. barkeri , M. paxii , M. albidulus , M. ruber , M. purpureus , and M. fumeus were evolutionarily close in the same clade with high bootstrap values. In another clade, several strains from M. purpureus , M. rutilus , M. aurantiacus , and M. kaoliang were clustered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRJEB20852), and M. pilosus MS-1, YDJ-2, YDJ-1, and K104061 (accession no. PRJNA718072; [ 13 ]), M. purpureus YY-1 (accession no. PRJNA453427) and M. purpureus NRRL 1596 (BCRC 31542 T ; accession no.…”
Section: Methodsmentioning
confidence: 99%